2022
DOI: 10.1007/s11356-022-23418-6
|View full text |Cite
|
Sign up to set email alerts
|

A decision fusion method based on classification models for water quality monitoring

Abstract: -Monitoring of water quality is one of the world's main intentions of countries. In this paper we present the use of Principal Component Analysis (PCA) combined with Support Vector Machines (SVM) and Artificial Neural Network (ANN) based on Decision Templates combination data fusion method. SVM and ANN are employed in classification stage. Decision Templates is applied to increase accuracy of the water quality classification compared to others combination data fusion methods. This work concerned the water qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…While machine learning algorithms like ANN and SVM offer simplicity, they struggle with non-linear relationships, posing challenges in capturing complex structures. Furthermore, the work of Ladjal et al [13] did not provide an interpretability mechanism for their model classifications. Khelil et al [14] compared the performance of SVM and the Long Short-Term Memory (LSTM) binary classifiers using the Tilesdit dam water quality data.…”
Section: Related Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…While machine learning algorithms like ANN and SVM offer simplicity, they struggle with non-linear relationships, posing challenges in capturing complex structures. Furthermore, the work of Ladjal et al [13] did not provide an interpretability mechanism for their model classifications. Khelil et al [14] compared the performance of SVM and the Long Short-Term Memory (LSTM) binary classifiers using the Tilesdit dam water quality data.…”
Section: Related Studiesmentioning
confidence: 95%
“…In the literature, several methods have been employed to classify water quality samples and determine their suitability for various purposes [13]- [17]. Ladjal et al [13] utilized artificial neural networks (ANN) and support vector machines (SVMs) to assess the quality of water from the Tilesdit dam.…”
Section: Related Studiesmentioning
confidence: 99%
“…Elkiran [37] analyzed and compared different integration techniques for Backpropagation Neural Network (BPNN), Adaptive Neuro-Fuzzy Inference System (ANFIS), Support Vector Machine (SVM) and Linear Autoregressive Integral Moving Average (ARIMA) models, applied to water quality modeling of Yamuna River in India, it proves that the performance of ANFIS model is better. Ladjal [38] proposed a data fusion method using Principal Component Analysis (PCA) in combination with Support Vector Machines (SVM), Artificial Neural Networks (ANN) and decision templates for water quality monitoring in the Tilesdit dam area in Algeria. The achieved classification accuracy was 98%.…”
Section: Plain Fusion Of Multiple Algorithmsmentioning
confidence: 99%
“…Solanki [9] analyzed and compared the application of deep learning algorithms and other unsupervised learning algorithms for classification of river pollution problems near Nasik, Maharashtra, India. Ladjal [10] proposed a data fusion method using principal component analysis (PCA) combined with support vector machines, artificial neural networks and decision templates for water quality classification and monitoring in the Tilesdit dam area in Algeria. The research found that SVM, The integration of ANN and PCA achieves a classification accuracy of 98%.…”
Section: Current Status Of Domestic and Foreign Researchmentioning
confidence: 99%